A Framework for Music-Speech Segregation using Music Fingerprinting and Acoustic Echo Cancellation Principle - Hussain, F.; Habib, H. A.; Khan, M. J. (The Nucleus, 2015)
Background interference creates voice intelligibility issue for listener. This research work considers background music as interference for communication through smart phone in areas with loud background music. This paper proposes a novel framework for background music segregation from human speech using music fingerprinting and acoustic echo cancellation. Initially, background music is searched in the database by music fingerprinting. Identified background music is registered and segregated using acoustic echo cancellation. Proposed approach generates better quality music speech segregation than existing algorithms. The research work is novel and segregates background music completely in comparison to existing approaches where single instruments are segregated successfully.